Pharmacokinetic interaction of riociguat and antiretroviral combination regimens in HIV-1-infected adults. (May 2019) - DeJesus, Edwin; Saleh, Soundos; Cheng, Sue; van der Mey, Dorina; Becker, Corina; Frey, Reiner; Unger, Sigrun; Mueck, Wolfgang
Riociguat, a first-in-class soluble guanylate cyclase stimulator, is approved for the treatment of pulmonary arterial hypertension (PAH), a serious potential complication of human immunodeficiency virus (HIV) infection. This open-label study investigated the pharmacokinetic drug–drug interaction potential of antiretroviral therapies on riociguat exposure in HIV-infected adults. HIV-infected adults without PAH on stable antiretroviral regimens (efavirenz/emtricitabine/tenofovir disoproxil, emtricitabine/rilpivirine/tenofovir disoproxil, elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil, abacavir/dolutegravir/lamivudine, or a ritonavir-boosted triple regimen) for ≥ 6 weeks received a single riociguat dose (0.5 mg). Riociguat pharmacokinetics and safety were assessed; pharmacokinetics was compared with historical healthy volunteer data. Of 41 participants treated (n = 8 in each arm, except n = 9 in the ritonavir-boosted triple regimen arm), 40 were included in the pharmacokinetic analyses. Riociguat median tmax was 1.00–1.27 h, with comparable maximum concentration (Cmax ) across the five background antiretroviral groups. Riociguat exposure was highest with abacavir/dolutegravir/lamivudine, followed by elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil > emtricitabine/rilpivirine/tenofovir disoproxil > ritonavir-boosted triple regimen > efavirenz/emtricitabine/tenofovir disoproxil; riociguat area under the plasma concentration versus time curve (AUC) was approximately threefold higher with abacavir/dolutegravir/lamivudine than efavirenz/emtricitabine/tenofovir disoproxil. Compared with historical data, riociguat exposure in HIV-infected adults was similar when co-administered with efavirenz/emtricitabine/tenofovir disoproxil, slightly increased when administered with ritonavir-boosted triple regimen and increased by approximately threefold when administered with abacavir/dolutegravir/lamivudine. Riociguat was well tolerated, with no new safety findings. Riociguat was well tolerated in adults with HIV on stable background antiretroviral therapy although an apparent increase in AUC of riociguat was observed in patients receiving abacavir/dolutegravir/lamivudine. Patients should be monitored closely during riociguat initiation and dose adjustment for signs and symptoms of hypotension.